Obsesive nightmare: economic crisis and Spanish transition to democracy through Political Cartoons (1974-1977) (Communication & Society, 2008)
This paper tries to study the way Spanish society looked at the economic crisis started at the second half of the 70’s and developed during the first steps of the Spanish transition to democracy. In order to research into the most spread topics and to discover which aspects of that crisis were considered most important, cartoons published by the main Spanish newspapers have been analysed. Those papers have been selected not only by their circulation, but also by their representation of different social groups or ideological tendencies.